2015
DOI: 10.1002/etc.2827
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water quality on zinc toxicity to the Florida apple snail (Pomacea paludosa) and sensitivity of freshwater snails to zinc

Abstract: The present study characterized the influence of water-quality characteristics on zinc (Zn) toxicity to the Florida apple snail (Pomacea paludosa) and the sensitivity of freshwater snails to Zn. Standard 96-h renewal acute toxicity tests were conducted with Zn and juvenile P. paludosa under 3 conditions of pH and alkalinity, water hardness, and dissolved organic carbon (DOC). Median lethal effect concentrations (96-h LC50s), no-observed- effect concentrations, lowest-observed-effect concentrations, LC10s, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Additionally, metal toxicity has been shown to depend on chemical speciation and geochemical factors, such as surface area for adsorption and redox active phases (e.g. hematite, goethite, and ferrihydrite) (Balistrieri et al, 2015;Gadd, 1992;Hoang and Tong, 2015;Meyer et al, 2015;Meyer et al, 2006;Moberly et al, 2010;Morton et al, 2000;Sani et al, 2003;Tipping and Lofts, 2015;Van Genderen et al, 2015). To better understand the influence of toxic metals on microbial communities, simultaneous characterization of both heavy metal speciation and microbial community is important.…”
Section: Pyrite [Fes 2 ] Chalcopyrite [Cufes 2 ]mentioning
confidence: 99%
“…Additionally, metal toxicity has been shown to depend on chemical speciation and geochemical factors, such as surface area for adsorption and redox active phases (e.g. hematite, goethite, and ferrihydrite) (Balistrieri et al, 2015;Gadd, 1992;Hoang and Tong, 2015;Meyer et al, 2015;Meyer et al, 2006;Moberly et al, 2010;Morton et al, 2000;Sani et al, 2003;Tipping and Lofts, 2015;Van Genderen et al, 2015). To better understand the influence of toxic metals on microbial communities, simultaneous characterization of both heavy metal speciation and microbial community is important.…”
Section: Pyrite [Fes 2 ] Chalcopyrite [Cufes 2 ]mentioning
confidence: 99%
“…Zinc toxicity has been studied extensively for aquatic organisms (Santore et al 2002;De Schamphelaere et al 2005;Hoang et al 2007aHoang et al , 2007bHoang and Klaine 2007;Hoang and Tong 2015;Lynch et al 2016;Van Regenmortel et al 2017;Perez and Hoang 2017). However, most aquatic toxicity studies have focused on individual species of invertebrates and/or fish.…”
Section: Introductionmentioning
confidence: 99%
“…Campbell and Stokes (1985) indicated that a decrease in pH inhibited biological uptake of Zn, Cu, and Cd to aquatic biota. However, some studies showed that the lowering toxicity with increasing pH in other aquatic organisms, due in part to decreasing of Zn bioavailability (De Schamphelaere and Janssen, 2004;Hyne et al, 2005;DeForest and Van Genderen, 2012;Hoang and Tong, 2015). Heijerick et al (2002) suggested that the effects of pH on Zn bioavailability should be taken into account the Zn speciation effect because the effect of Zn toxicity was mainly depending on dissolved Zn, not on free Zn.…”
Section: Influence Of Water Chemistry On Zn Bioavailabilitymentioning
confidence: 99%
“…Heijerick et al (2002) suggested that the effects of pH on Zn bioavailability should be taken into account the Zn speciation effect because the effect of Zn toxicity was mainly depending on dissolved Zn, not on free Zn. The Zn 2þ , ZnOH þ , ZnCO 3 , and ZnHCO 3 are considered to be the bioavailable aqueous Zn species that depend on the pH level (DeForest and Van Genderen, 2012;Hoang and Tong, 2015). The implication for determination of Zn bioavailability and toxicity in the Zn-BLM should be incorporated with pHdependent stability constants of Zn species.…”
Section: Influence Of Water Chemistry On Zn Bioavailabilitymentioning
confidence: 99%